THE INFLUENCE OF OCCUPATIONAL SAFETY & HEALTH AND WORK SUPERVISION ON EMPLOYEE WORK PERFORMANCE - Rudyanto Simanjuntak; Vanessa Vicario (PT. MITRA ANGKASA INFORMATIKA, 2024)
The progress of the company can be seen from the achievements given by employees because the achievements are the result of what employees produce whether in accordance with or not with company expectations. But the ability to excel in each employee is different because it is caused by individual abilities, jobs provided and facilities provided by the company. The method used in this research is quantitative descriptive. The population and sample of this study were all employeesof , amounting to 38 people. Questionnaire processing is measured with a Likert scale. The model of data analysis used to answer hypotheses is multiple regression. The results showed that partially and simultaneously the Occupational Safety & Health (K3) and work supervision variables had a significant effect on the employee work performanceof . The magnitude of the influence of the independent variables in explaining the variation of the dependent variable is 54.7% the remaining 45.3% is influenced by other variables besides the variables in this study such as: incentives, leadership, organizational commitment, motivation and other variables Keywords: Occupational Safety & Health (K3), Work Supervision, Employee Work Performance.